Entrepreneurship education and self-employment intentions: A conditional effect of entrepreneurial self-efficacy evidence from a developing country - Moses Kisame Kisubi; Ronald Bonuke; Michael Korir (Cogent Business & Management, 2021)
To determine the moderating effect of entrepreneurial self-efficacy (ESE) in the relationship between entrepreneurship education (EE) and self-employment intentions (SEI). Explanatory survey design together with systematic sampling technique were utilized to collect data from a sample of 458 undergraduate finalists from Makerere and Kyambogo Universities in Uganda. Data were analyzed using Hayes' PROCESS macro vs3.2 (Model 4). Results of the study indicate that entrepreneurship education and entrepreneurial self-efficacy are significant predictors of students' self-employment intentions. The study also found a buffering moderating effect of entrepreneurial self-efficacy significantly in the relationship between entrepreneurship education and self-employment intentions. The study contributes to the extant literature by confirming the relationship between the study variables and supporting both SCT and TPB. Besides, the study provides new insights concerning the moderating role of ESE in the relationship between EE and SEI. Educators, curriculum developers, and university management need to conduct a students' entrepreneurial competence needs assessment before, such that the entrepreneurial course is customized to the needs of the students other than a generalized and standardized entrepreneurial course. The study provides new insights on the conditional effect of ESE on the link between EE and SEI in the context of a developing country.
Keywords: 650; Entrepreneurship education; entrepreneurial self-efficacy; self-employment intentions; students